Proceedings. (ICASSP '05). IEEE International Conference on Acoustics, Speech, and Signal Processing, 2005.
DOI: 10.1109/icassp.2005.1415664
|View full text |Cite
|
Sign up to set email alerts
|

A Family of Selective-Tap Algorithms for Stereo Acoustic Echo Cancellation

Abstract: The use of adaptive lters employing tap-selection for stereophonic acoustic echo cancellation is investigated. We propose to employ subsampling of the tap-input vector, that is intrinsic to partial update schemes, to improve the conditioning of the tap-input autocorrelation matrix hence improving convergence. We investigate the effect of MMax tap-selection on the convergence rate for the single channel case by proposing a new measure which is then used as an optimization parameter in the development of our ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…3, for , increases smoothly and consequently the degradation in steady-state performance is negligible. This property has been exploited in the exclusive-maximum (XM) tap selection, which has been deployed in SAEC algorithms to give good convergence performance such as presented in [13] and [14]. In addition, we have shown that under time-varying unknown system conditions, there exists for NLMS and MMax-NLMS, an optimal step-size given by (29) and (56), respectively, which jointly maximizes the performances in terms of low misalignment and high convergence rate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3, for , increases smoothly and consequently the degradation in steady-state performance is negligible. This property has been exploited in the exclusive-maximum (XM) tap selection, which has been deployed in SAEC algorithms to give good convergence performance such as presented in [13] and [14]. In addition, we have shown that under time-varying unknown system conditions, there exists for NLMS and MMax-NLMS, an optimal step-size given by (29) and (56), respectively, which jointly maximizes the performances in terms of low misalignment and high convergence rate.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown in [13] that the performance of MMax-NLMS degrades only gracefully with reducing compared to fully updated NLMS. For , the degradation in performance can be insignificant.…”
Section: A Mmax-nlms Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of taps selected in the sub-filterĤ r (k, ) is finally determined by substituting (26) in (19).…”
Section: Dynamic Effort Allocation (Dea)mentioning
confidence: 99%
“…The most common approach to tackle the misalignment problem is to decorrelate the tap-inputs, for which several techniques have been proposed in literature [3,15,17]. Tap selection schemes such as the exclusive-maximum (XM) [18][19][20] have also been proposed to specifically tackle the misalignment problem for stereo AEC applications. The XM scheme improves the conditioning of the tap-input covariance matrix via exclusive updates of the two adaptive filters, i.e., in each iteration the same filter tap index is never selected in both channels.…”
Section: Introductionmentioning
confidence: 99%